Radiofrequency: Use of aesthetic applications against skin aging (Research, Society and Development, 2022)
Radiofrequency (RF) aesthetic applications offer a variety of options for both the physician and the patient. Technologies continually advance, as does understanding how these devices work, so phasing out older devices and adopting newer ones is something to look forward to. RF is considered an advance in aesthetic technology, since it can be used for aesthetic treatments of anti-aging without cuts and with low levels of lesions. Monopolar RF devices use a high frequency electrical current. Bipolar devices, on the other hand, consist of 2 electrodes, without a grounding plate, emitting a fast alternating current at a predetermined distance. Multipolar devices use 3 or more electrodes to deliver thermal energy to dermal and subdermal tissue. The multi-generator RF devices are built on the proprietary RF delivery technology released by Endymed Medical. Finally, it is understood that there are several generations of radiofrequency devices for non-invasive aesthetic treatments. Devices differ in the number of electrodes and additional energy modalities that combine to maximize clinical effects and minimize adverse effects. Given this context, the objective of this study is to demonstrate the aesthetic applications of the use of RF in dermatological treatments, emphasizing its results and application safety. Ante este contexto, el objetivo de este estudio es demostrar las aplicaciones estéticas del uso de RF en tratamientos dermatológicos, enfatizando en sus resultados y seguridad de aplicación.